SYNTACTIC FUNCTIONS OF AS IN ENGLISH - asridayani asridayani (Krinok:Jurnal Linguistik Budaya, 2017)
The research is the result of a study which concerned with syntactic functions of as in English. The major purpose of this research is to provide as clear as possible some related aspects concerning the syntactic functions of as in English.  This research is based on the data obtained from references written by various outstanding linguists. This research uses the theory based on Herbert (1990) which calls this kind of study a library research  and the theory related to the classification of as is adopted from Quirk (1973 and 1985). The data collection is conducted in several steps such as administrating some sentences, checking and verifying the data with the intuition of the writer herself and also with the theories given by various linguistis. All sentences given in the examples are presented in the written form without their phonetic transcription. This research report is presented in the descriptive form which qualitative in nature, and thus, the method applied in this study is following Herbert (1990) which called descriptive research.The functions of as in this research are as a subordinator to introduce complex sentences indicating adverb clauses such as adverb clause of time, adverb clause of concession or supposition, adverb clause of comparison of degree, adverb clause of comparison of manner, adverb clause of cause or reason, adverb clause of condition, adverb clause purpose, and adverb clause of result, as a preposition, as an intensifier and it may also be used in subjunctive mood. Keywords: as, syntactic function.